Policy Implementation in the Preparation of Financial Statements at Makassar State University - Asmilah Abdullah (Jurnal Office, 2022)
Implementation can be interpreted as an activity to carry out a policy as outlined in a regulation issued by the government or other state institutions in order to achieve the objectives outlined in the policy. The purpose of this research is to find out and analyze how the implementation of policies in the preparation of financial statements at Makassar State University. This research was conducted with a qualitative approach. The data collection techniques used in this research are observation, interviews, and document review. Data analysis techniques used in this research are data reduction, data presentation and conclusions/verification. The results of this study indicate that employees in the Finance/Accounting section of UNM, where on average they have understood what is meant by Accrual-Based SAP even though their level of understanding varies. is in accordance with the main duties and functions of each implementer of financial statement preparation, and the preparation of financial statements at the Makassar State University is prepared by the Financial Reporting Accounting Team assisted by the Assistant Expenditure Treasurer (BPP) of Makassar State University and coordinates with the expenditure treasurer, revenue treasurer , salary staff, and others related to the accounts contained in the financial statements.